New Trends in Workforce Competences Due to the Internationalization of Markets - BUTUM, Lavinia Cornelia (Management Dynamics in the Knowledge Economy, 2018)
The demand for competences recognized internationally has been growing, since many Romanian companies are developing their business in a diverse and multinational environment. This is also a consequence of multinationals and labor market development, in Romania, in recent years. Today’s employee is a combination of a high skilled professional and an adaptable person that is able to accomplish different tasks and to solve a variety of issues. Those abilities are completed with creativity and optimization of work, necessary for taking part in new projects and, not the least, for providing innovation for the company. In this regard, the present paper aims to analyze and to compare the European and Romanian graduates’ mobility in view of obtaining the desired job, the dynamics of competences and the role of future specialization in an international environment.